DEVELOPING A PREDICTIVE MODEL OF SOCIAL COGNITIVE INFLUENCES ON PHYSICAL ACTIVITY IN MIDDLE-AGED AND OLDER ADULTS: A CROSS-SECTIONAL STUDY - Arovah, Novita Intan; Kurniawaty, Juni; Haroen, Hartiah (Universitas Airlangga, 2025)
Introduction: Increasing physical activity levels in middle-aged and older adults is a critical public health agenda, as regular physical activity reduces morbidity, healthcare costs, and chronic disease risks by up to 90%. Developing effective physical activity programs, however, requires comprehension of factors influencing physical activity behavior. Aims: This research aimed to develop a predictive model of social cognitive influences on moderate and vigorous physical activity (MVPA) in this demographic. Method: A cross-sectional study was conducted in 118 participants, 76% of whom were female. Social cognitive factors, which included self-efficacy, outcome expectations (physical, social, and self-evaluation), self-regulation (goal setting and planning), and social support (from family and friends) regarding physical activity, were assessed using validated self-reported questionnaires. A 7-day Physical Activity Recall interview was conducted to measure MVPA. Data were analyzed using bivariate correlations and stepwise multiple linear regressions, adjusted for sex and age. Results: All social cognitive measures showed moderate to strong correlations with MVPA (r = 0.43-0.79). The regression model, which included self-efficacy, physical outcome expectations, planning, and social support, explained 77% of the variance in MVPA. Conclusion: These results highlight the importance of strengthening these social cognitive factors to encourage more physically activity among middle-aged and older adults in Indonesia.